Best Periodic Proximity Points for Cyclic Weaker Meir-Keeler Contractions - Chiming Chen; Chingju Lin (Journal of Applied Mathematics)
The purpose of this paper is to present the existence of the best period proximity point for cyclic weaker Meir-Keeler contractions and asymptotic cyclic weaker Meir-Keeler contractions in metric spaces.